Study of Slow Sand Filtration in Removing Total Coliforms and E.Coli - Ekha Yogafanny; Stephan Fuchs; Ursula Obst (Teknik Lingkungan Universitas Islam Indonesia, 2014)
This study was aimed to evaluate the performance of SSF in removing bacteria (Total Coliforms and E. Coli) in regard to grain size distribution and grain shape intermittently. Two methodological approaches used in this reasearch were literature review and laboratory work. Bacteria removal was analyzed considering two different filter media (Rhine sand-spherical shape and Lava sand-angular shape) with three different grain size distributions. The best performance was attained by filter column F4 which consisted of Lava sand and had the configuration C2 (d10 = 0.07 mm; Cu = 4.2). This filter column achieved 4.7log-units removal of Total Coliforms and 5.0log-units removal of E. coli. The results show that a smaller grain size and an angular shape of sand grain lead to an increase in bacteria removal.